Antidiabetic evaluation of Artocarpus odoratissimus (Moraceae) fruit - Kay Ann S. Jonatas; Joseph Mari B. Querequincia; Shiela D. Miranda; Ukoba Obatavwe; Mary Jho-Anne Corpuz; Ross D. Vasquez (Jurnal Ilmiah Farmasi, 2020)
Background: Diabetes mellitus causes 4.2 million of deaths worldwide and 79% adults with diabetes are living in low- and middle-income countries. This research providing an alternative therapy through the prevention of postprandial hyperglycemia may help diabetic patients and provide a new utilization model of fruit peel. Artocarpus odoratissimus, commonly known as marang, is an edible fruit found in the southern part of the Philippines. Most of the weight of the fruit is discarded and treated as waste.Objectives: This study aimed to utilize the by-products of marang fruit as a promising pharmaceutical agent by determining the phytochemicals present and in vitro antidiabetic activity of the different parts of the fruit.Methods: Phytochemical screening of phenolics and flavonoids was done through thin layer chromatography. Ten concentrations (2-1000 µg/mL) of the extracts from the peel, pulp, and seeds were evaluated for the in vitro antidiabetic assay using alpha-glucosidase enzyme. Mean percent inhibition was calculated, and data was analyzed using ANOVA. The IC50 estimates were calculated using the program GraphPad Prism version 8.Results: Extracts from the fruit parts of A. odoratissimus contained phenols and flavonoids and were active inhibitors of alpha-glucosidase enzyme. The fruit peel extract of marang was the most potent (IC50 = 48.19 µg/mL) compared to the seed extract, pulp extract, and the standard drug acarbose (p value = 0.035).Conclusion: The fruit waste, the peel and seeds, has an intense activity against alpha-glucosidase enzyme because of their phenols and flavonoid contents.Keywords: alpha-glucosidase, Artocarpus, diabetes, phenolics, fruit peel